Cannabidiol Modulates Neuroinflammatory and Estrogen-Related Pathways in a Sex-Specific Manner in a Chronic Stress Model of Depression - Uri Bright; Irit Akirav (Cells)
Evidence indicates a bidirectional link between depressive symptoms and neuroinflammation. This study evaluated chronic cannabidiol (CBD) treatment effects in male and female rats subjected to the unpredictable chronic mild stress (UCMS) model of depression. We analyzed the gene expression related to neuroinflammation, cannabinoid signaling, estrogen receptors, and specific microRNAs in the ventromedial prefrontal cortex (vmPFC), CA1, and ventral subiculum (VS). UCMS influenced immobility in a sex-specific manner, increasing it in males and decreasing it in females, effects that were reversed by CBD. CBD also normalized the UCMS-induced upregulation of tumor necrosis factor α (TNF-α) in the CA1 and VS in males. In both sexes, UCMS induced the upregulation of the nuclear factor kappa B subunit 1 (NF-κB1) gene in the VS, which was unaffected by CBD. Additionally, CBD reversed CB1 downregulation in the VS of males but not in the vmPFC of either sex. In males, CBD restored the UCMS-induced downregulation of VS estrogen receptor genes ERα and ERβ. UCMS also altered miR-146a-5p expression, downregulating it in females (VS) and upregulating it in males (CA1), with no CBD effect. These findings highlight the sex-specific mechanisms of CBD’s antidepressant effect, with hippocampal neuroinflammatory and estrogenic pathways playing a key role in males.